Correction: Synthesis, structural characterization, electrochemical behavior and anticancer activity of gold(iii) complexes of meso-1, 2-di(1-naphthyl)-1, 2-diaminoethane and tetraphenylporphyrin. (2nd July 2020) - Altaf, Muhammad; Ahmad, Saeed; Kawde, Abdel-Nasser; Baig, Nadeem; Alawad, Abdullah; Altuwaijri, Saleh; Stoeckli-Evans, Helen; Isab, Anvarhusein A.
Abstract : Correction for 'Synthesis, structural characterization, electrochemical behavior and anticancer activity of gold(iii ) complexes of meso -1, 2-di(1-naphthyl)-1, 2-diaminoethane and tetraphenylporphyrin' by Muhammad Altaf et al., New J. Chem., 2016, 40, 8288–8295, DOI: ; 10.1039/C6NJ00692B .